Biological versus chronological ovarian age: implications for assisted reproductive technology - Tredway Donald; Howles Colin M; Humaidan Peter; Alviggi Carlo; Hillier Stephen G (BMC, 2009)
Abstract Background Women have been able to delay childbearing since effective contraception became available in the 1960s. However, fertility decreases with increasing maternal age. A slow but steady decrease in fertility is observed in women aged between 30 and 35 years, which is followed by an accelerated decline among women aged over 35 years. A combination of delayed childbearing and reduced fecundity with increasing age has resulted in an increased number and proportion of women of greater than or equal to 35 years of age seeking assisted reproductive technology (ART) treatment. Methods Literature searches supplemented with the authors' knowledge. Results Despite major advances in medical technology, there is currently no ART treatment strategy that can fully compensate for the natural decline in fertility with increasing female age. Although chronological age is the most important predictor of ovarian response to follicle-stimulating hormone, the rate of reproductive ageing and ovarian sensitivity to gonadotrophins varies considerably among individuals. Both environmental and genetic factors contribute to depletion of the ovarian oocyte pool and reduction in oocyte quality. Thus, biological and chronological ovarian age are not always equivalent. Furthermore, biological age is more important than chronological age in predicting the outcome of ART. As older patients present increasingly for ART treatment, it will become more important to critically assess prognosis, counsel appropriately and optimize treatment strategies. Several genetic markers and biomarkers (such as anti-Müllerian hormone and the antral follicle count) are emerging that can identify women with accelerated biological ovarian ageing. Potential strategies for improving ovarian response include the use of luteinizing hormone (LH) and growth hormone (GH). When endogenous LH levels are heavily suppressed by gonadotrophin-releasing hormone analogues, LH supplementation may help to optimize treatment outcomes for women with biologically older ovaries. Exogenous GH may improve oocyte development and counteract the age-related decline of oocyte quality. The effects of GH may be mediated by insulin-like growth factor-I, which works synergistically with follicle-stimulating hormone on granulosa and theca cells. Conclusion Patients with biologically older ovaries may benefit from a tailored approach based on individual patient characteristics. Among the most promising adjuvant therapies for improving ART outcomes in women of advanced reproductive age are the administration of exogenous LH or GH.